2016
DOI: 10.1177/0265532215594643
|View full text |Cite
|
Sign up to set email alerts
|

Elicited imitation as a measure of second language proficiency: A narrative review and meta-analysis

Abstract: Elicited imitation (EI) has been widely used to examine second language (L2) proficiency and development and was an especially popular method in the 1970s and early 1980s. However, as the field embraced more communicative approaches to both instruction and assessment, the use of EI diminished, and the construct-related validity of EI scores as a representation of language proficiency was called into question. Current uses of EI, while not discounting the importance of communicative activities and assessments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
115
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(133 citation statements)
references
References 61 publications
9
115
0
Order By: Relevance
“…Results of RQ3 showed that the only significant predictor of item difficulty was sentence length, accounting for almost 45% of the variance in EIT scores. This finding supports the results of Yan et al.’s () recent meta‐analysis which showed that “EI tasks with varied sentence length will more likely match the ability of speakers with different proficiency levels” (p. 26). The regression model was also in line with the findings from Graham et al.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Results of RQ3 showed that the only significant predictor of item difficulty was sentence length, accounting for almost 45% of the variance in EIT scores. This finding supports the results of Yan et al.’s () recent meta‐analysis which showed that “EI tasks with varied sentence length will more likely match the ability of speakers with different proficiency levels” (p. 26). The regression model was also in line with the findings from Graham et al.…”
Section: Discussionsupporting
confidence: 87%
“…Next, a hierarchical multiple regression was run to determine to what extent the selected features predicted variance in EIT scores. Based on previous literature demonstrating the importance of sentence length in determining item difficulty (e.g., Yan et al., ), the number of syllables variable was entered first in block 1 and the number of embedded clauses and vocabulary scores variables were entered together in block 2. The hierarchical regression yielded a significant model, F (1, 28) = 22.807, p < .001 r = .670, r 2 = .449.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations